Spatio-temporal analysis of land use and land cover changes in arid region of Saudi Arabia - Albalawi, E.; Dewan, Ashraf; Corner, Robert (The Geomate International Society, 2018)
© 2018, Int. J. of GEOMATE. Changes in land use/land cover (LU/LC) are a major factor driving global environmental change, especially in arid and semi-arid regions. As a result, expansion of agriculture and urbanization is occurring in ecologically fragile lands. This paper analyzed and assessed land use/land cover changes in an agricultural center Tabuk in Saudi Arabia, object-based classification technique (OBC) using Landsat images for seven years (1985, 1990, 1995, 2000, 2005, 2009, and 2015) were used for LU/LC analysis. The urban growth type for Tabuk was measured using Urban Growth Analysis Tool (UGAT) within a GIS. The study found an increase in urban areas from 48 km 2 in 1985 to 315 km 2 in 2015. A significant increase of 61% in agricultural land, from 1985 (112 km 2 ) to (577 km 2 ) in 2015. This expansion is occurring at the expense of the barren land with a loss of 768 km 2 . An overall classification accuracy ranged from 94% to 97% across all images. The urban growth type for Tabuk was determined as 72% to be of the extension-type over the study period, with urban areas expanding in a direction towards the northwest and west area. Assessing spatial and temporal LU/LC change has aided to understand the impacts of expanding agriculture and urban areas. The LU/LC maps could aid government planners and decision-makers to analyze and manage agricultural and urban growth.